1989
DOI: 10.1007/bf00249612
|View full text |Cite
|
Sign up to set email alerts
|

Paired-pulse facilitation and inhibition in the dentate gyrus is dependent on behavioral state

Abstract: It is well established that neuronal transmission from the entorhinal cortex through the dentate gyrus via the perforant path is dependent on behavioral state. To further study the modulation of neuronal transmission by behavioral state we employed the paired-pulse technique to study interneuronally-mediated inhibition and short-term facilitation in the dentate gyrus of freely-moving rat preparations. Precisely timed double pulses of electrical stimulation were delivered to the perforant path in the chronicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 48 publications
1
14
0
1
Order By: Relevance
“…This short form of synaptic plasticity consists of the application of two stimuli with a relatively short interstimulus interval. The second response is reduced when the interstimulus interval is <50 ms, probably by recurrent inhibitory interneurons; or increased when the interstimulus interval is above 50 ms, an effect attributed to an increased presynaptic Ca ++ concentration (Almaguer et al, ; Almaguer‐Melian et al, ; Austin et al, ). Earlier published data show an increase in PPF ratio under EPO (Adamcio et al, ; Kamal et al, ), but we fail to found any EPO‐induced changes (administered 15 min before the start the study) in paired‐pulses inhibition or facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…This short form of synaptic plasticity consists of the application of two stimuli with a relatively short interstimulus interval. The second response is reduced when the interstimulus interval is <50 ms, probably by recurrent inhibitory interneurons; or increased when the interstimulus interval is above 50 ms, an effect attributed to an increased presynaptic Ca ++ concentration (Almaguer et al, ; Almaguer‐Melian et al, ; Austin et al, ). Earlier published data show an increase in PPF ratio under EPO (Adamcio et al, ; Kamal et al, ), but we fail to found any EPO‐induced changes (administered 15 min before the start the study) in paired‐pulses inhibition or facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Paired-pulse responses in the granule cells of the dentate gyrus (Austin et al, 1989) and pyramidal cells in CA1 (Cao and Leung, 1991) were enhanced during walking and rapideye-movement sleep as compared to awake immobility and slow-wave sleep. The largest enhancement of the population spike occurred at about 30-50 ms interpulse interval (Green et al, 1987;Cao and Leung, 19911, corresponding to 20-33 Hz.…”
Section: Fast Rhythms In Evoked Potentials and Unit Firingmentioning
confidence: 89%
“…Thus, while low-frequency transmission is suppressed, high-frequency transmission will be enhanced. Both synaptic potentials in the dentate gyrus (Winson & Abzug, 1978) and paired-pulse phenomena (Austin, Bronzino & Morgane, 1989) are dependent on behavioural state. Histaminergic neurons fire according to behavioural state and have been strongly implicated in central arousal mechanisms (Lin et al 1988;Wada et al 1991).…”
Section: Discussionmentioning
confidence: 99%